Assessment of void fraction models and correlations for subcooled boiling in vertical upflow in a circular tube. (June 2021) - Cai, Chang; Mudawar, Issam; Liu, Hong; Xi, Xi
Highlights: A comprehensive review of void fraction related models and correlations is provided. Aside from void fraction, the review includes net vapor generation point and vapor quality. Predictive accuracy of prior models and correlations is based on comparison with a new consolidated database. A new void fraction correlation is proposed which shows superior overall predictive accuracy. Abstract: This paper provides a comprehensive review as well as assessment of accuracy of published models and correlations for net vapor generation point, vapor quality, and void fraction in subcooled vertical upflow boiling in a circular tube. Also provided is a detailed discussion on the rationale and physical mechanisms upon which the individual predictive methods are based. The assessment is accomplished by comparing predictions to a new consolidated database consisting of 61 data points for thermodynamic equilibrium quality at the net vapor generation point, amassed from 5 sources, and 1118 data points for void fraction, from 11 sources. Overall, it is shown that correlations by Saha and Zuber provide best predictions for both thermodynamic equilibrium quality at the point of net vapor generation and axial distribution of vapor quality. In terms of void fraction prediction, best accuracy among prior predictive methods is achieved, in order, using a slip ratio model by Thom, drift-flux model by Dix, slip ratio model by Ahmad, and modified homogeneous model by Nishino and Yamazaki. It is shown that the vast majority of models and correlations show far better accuracy over the higher range of void fraction of 0.20-1.0 than the low range of 0-0.2. A new and simple void fraction correlation spanning the entire range of flow conditions of the consolidated database is proposed, which is shown to yield superior overall predictive accuracy compared to prior models and correlations. Finally, a step-by-step procedure for calculating void fraction with best accuracy is presented.